Pengaruh inflasi, investasi asing langsung dan pengeluaran pemerintah terhadap pertumbuhan ekonomi Indonesia - Riris Prantika Putri; Heriberta Heriberta; Emilia Emilia (Jurnal Paradigma Ekonomika, 2018)
This study aims to analyze the development of inflation, foreign direct investment (FDI) and government expenditure to economic growth in Indonesia also to identify and analyze the effect of inflation, FDI and government expenditure to economic growth in Indonesia. The data used is secondary data in the form of time series. Based on the data obtained, the average development of economic growth in Indonesia during the period 2000-2017 was 5.29%. Based on the F test the independent variables tend to influence the dependent variable. In the t-test is known that inflation does not affect the economic growth in Indonesia, while FDI and government expenditure has a positive and significant impact on economic growth in Indonesia. The R2 value is 0,594602, amounting to 59.46% means that economic growth is affected by inflation, FDI and government expenditure, 40.54% influenced by other factors that were not included in this study